Analysis of Foreman Performance Factors on the Success of Residential Building Construction Projects - Deri Muharam; Edison H Manurung; Kerlima Hutagaol; S. Wardiningsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
The main focus of productivity in the construction industry is labor productivity, because labor is the resource that has the greatest influence on management. In this case the effort made by an employee is a physical form of motivation, the higher the employee's motivation, the greater the effort he does. This study aims to find out every need that is a top priority that influences the motivation of the Residential House Development project workers. The method used in this study is analytical descriptive, meaning that data is collected and compiled first, then explained and analyzed until finally conclusions are drawn on the existing problems. Data processing uses the computer program SPSS (Statistics Product and Service Solution) version 15.00. Data analysis techniques using validity, reliability, frequency tests, from the analysis it can be seen that bonuses and additional wages are a top priority for physical needs with a total score of 159, good work safety programs are a top priority for security and safety needs with a total score of 148, Relationship Good with fellow workers is a top priority for Social Needs with a total score of 148. Being able to complete work well is a top priority for Recognition Needs with a total score of 145. Good arrangement of work schedules is a top priority for self-identity needs with a total score of 139. Alternatives to increasing worker motivation is by providing bonuses and additional wages when construction workers can complete work before the target.